Dynamics of Employee Performance: The Influence of Compensation and Organizational Culture Through Motivation as a Mediator at PT Mana Jaya Makmur Mojokerto - Suparman, Suparman; Santoso, Rahmat Agus; Desembrianita, Eva (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
The aim of this research is to examine the influence of compensation and organizational culture on employee performance with motivation as a mediating variable at PT Mana Jaya Makmur Mojokerto. The type of research used in this research is quantitative research with the population and sample in this research being company employees totaling 300 respondents. The results of the research show that compensation does not have a positive and significant effect on employee performance, organizational culture has a positive and significant effect on employee performance, compensation and organizational culture have a positive and significant effect on motivation, and motivation has a positive and significant effect, while the effect is indirect. Compensation for organizational performance through motivation and motivation can function as a full mediation considering that the indirect influence is greater than direct care, but work culture on employee performance does not require motivation as a mediator because the direct influence is greater, so it is very important to pay attention to the need for existing motivation. provided and increased through allowances.